The Influence of the Contextual Learning Model Type of Modeling Assisted by Role-Playing Techniques on the Storytelling Skills of PGSD Students at Sanata Dharma University - Fatikasari, Addina Nasihah; Mustadi, Ali; Nugroho, Ikhlasul Ardi; Kartono (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to determine the effect of contextual learning models using role-playing techniques on the storytelling skills of Sanata Dharma University PGSD (Primary School Teacher Education) students. This research uses a quantitative approach to experimental methods by designing a group pretest and posttest. The population in this research is all PGSD students at Sanata Dharma University for the 2022–2023 academic year. The sampling technique uses simple random sampling. The sample taken was class 2C, with a total of 43 students. Data collection was carried out using observation and tests. This research data analysis technique uses prerequisite tests, namely the normality test, and hypothesis tests, namely the sample T-test. The findings in this research show that the application of a contextual learning model assisted by role-playing techniques has a significant positive effect on the storytelling skills of PGSD students at Sanata Dharma University. This can be seen from the average pretest score of students before implementing the contextual learning model, a modeling type assisted by role-playing techniques, namely 60.12 in the sufficient category. Meanwhile, the posttest average was 83.02 in the good category. Based on the normality test, the data results were normally distributed. A hypothesis-testing paired sample t-test was also carried out and produced a sig = 0.000 value, which means it is smaller than α (0.05). Thus, H0 was rejected and Ha was accepted. Furthermore, this research recommends that lecturers apply this learning model as an innovative model that can be applied to improve students' storytelling skills.